Peranan Kompetensi Dalam Meningkatkan Kinerja Karyawan PT. Summit Oto Finance - Shandra Bahasoan (MBIA, 2019)
The study was conducted aimed at knowing the role of competencies, namely knowledge, skills and self-concept in improving the performance of employees of PT. Summit Oto Finance, with a sample of 54 people . The method used in this study using questionnaires, interviews and documentation. Research approach by using quantitative descriptive method by analyzing Multiple Linear Regression to measure the performance of employees of PT. Summit Oto Finance. The results of this study simultaneously independent competency variables consisting of knowledge, skills and self-concept have a positive and significant influence on the dependent variable,namely employee performance. From the test results the correlation of the influence of competencies on employee performance is 94.1 percent while 5.9 percent is influenced by other factors. Dominant competencies affect the performance of employees of PT. Summit Oto Finance is a skill.